Care or neglect of burs: A comparative study of different sterilization methods - H R Pooja; Priya Nagar; Andrea Natalia Mascarenhas; C H. Chandana Krishna Shree (Wolters Kluwer Medknow Publications, 2022)
Background: Burs are unique by virtue of their complex architecture which makes precleaning and sterilization difficult to achieve. Inadequate sterilization causes cross infection. Aim: The aim of the present study was to assess and compare the effectiveness of various sterilization methods of dental diamond burs commonly utilised in dental practice. Methodology: The current study was done to investigate the efficacy of four decontamination methods on fifty diamond burs. These burs were used among ten patients who were indicated for pulp therapy in primary deciduous molars. Access cavity preparation was prepared using dental burs and divided into five groups: Group I - being control group (unsterilized), Group II - Contaminated burs sterilized using 2% glutaraldehyde, Group III -Contaminated burs sterilized in autoclave, Group IV - Contaminated burs sterilized in ultraviolet steriliser, and Group V - Contaminated burs sterilized using 70% isopropyl alcohol. All the burs were immersed in the Brain − Heart Infusion broth, incubated for 24 h at 37°C to check the sterility of burs. Bacterial culture (Broth turbidity) was then measured for its optical density (OD) using the spectrophotometer. OD values reading were recorded and statistical analysis was done using Kruskal-Wallis test and Mann-Whitney's post hoc TEST. Results: Among all decontamination methods, 2% glutaraldehyde and autoclave showed the most significant change in microbial load compared to the other group at P < 0.001. Conclusion: Sterilization with 2% glutaraldehyde followed by autoclave of dental burs is the key step in achieving success in the endodontic procedures with less microbial load which determines the success of pulpectomy procedures.